Clinical, pathomorphological and immunohistochemical evaluation of tissue repair in diabetic foot ulcers - Alla Y. Tokmakova; Ekaterina L. Zaitseva; Iya A. Voronkova; Marina V. Shestakova (Сахарный диабет)
Background: It is known that wound healing is Impaired in diabetes mellitus. Possible reasons are widely being searched. However, despite all the available data, reliable markers of reparative processes in diabetes mellitus are needed to be found. Aim: To study morphological and some immunohistochemical markers of tissue repair in patients with diabetic foot ulcers after local treatment. Materials and methods: 70 patients with diabetic foot ulcers before and after surgical debridement were included. Histological (light microscopy) and immunohistochemical (CD68, MMP-9, TIMP-1) characteristics of tissue repair processes in soft tissues of the lower extremities in patients with diabetes mellitus were analyzed. Histological and immunohistochemical examination of soft tissues were performed in 63 patients before and after surgical debridement and 10 days after local treatment. Results: After the surgical debridement a significant reduction in the area of wounds was registered by 23.4% (p <0.05), wound depth by 29.4% (p <0.05). Based on the results of the morphological study, the presence of mature granulation tissue in the wounds was confirmed. Immunohistochemical study of wound biopsies demonstrated a significant decrease in proteolytic activity in the wound as a decrease in MMP-9 expression (p <0.05). Statistically significant changes in the number of macrophages against the initial data were not found, as well as increased expression of TIMP-1 was observed (p> 0.05 and <0.05, respectively). Conclusion: According to the data, there was a significant decrease in the area and depth of wounds during local treatment. The intensity of tissue repair was confirmed by the results of histological and immunohistochemical studies. However, the absence of a statistically significant change in the amount of macrophages on the background of treatment suggests that this repair link is disrupted in diabetes mellitus, which is the reason for the "chronic" wounds and requires further studies.